FACTORS INFLUENCING THE OCCURRENCE OF FRAUDULENT FINANCIAL REPORTING: PERSPECTIVE OF FRAUD PENTAGON THEORY - Budiman Teri; Ratna Ayu Damayanti; Sri Sundari (Contemporary Journal on Business and Accounting, 2022)
Purpose – This study aims to examine and analyze the effect of compensation suitability, leadership style, internal control system, unethical behavior, competences, and job dualism against the tendency to commit fraudulent financial reporting on Provincial Government of South Sulawesi. Design/methodology/approach – This research uses a quantitative approach. Analysis method that used to test the hypothesis is multiple linear regression. Findings – The result of this study shows that leadership style, unethical behavior, competence, and job dualism has impact against the tendency to commit fraudulent financial reporting; meanwhile compensation suitability and internal control system has not impact against the tendency to commit fraudulent financial reporting. Originality – Collecting data in this study through questionnaires and conducted on 62 respondents who were employee at Provincial Government of South Sulawesi.